Doing business in the United Arab Emirates - Noack, Sascha Ralf (2012)
The purpose of this thesis is to illustrate important considerations, as well as outlining the decisions that need to be made when considering starting to do business in the United Arab Emirates (U.A.E). Furthermore it offers an overview of the prevalent political, legal, social and economical environments that are an important basis for making the decision to expand to that region. After describing country-specific variables of the U.A.E., the business environment including business culture, industry sectors, legal and fiscal conditions, and various possible business forms will be analysed. The insights gained will be used to suggest business opportunities and to develop concrete steps on how to start business relations and set up a business in the U.A.E.